A study aiming at working out the standard and methodology of mapping in the comprehensive land use planning at village and town level - OU Hai-ruo; WU Ci-fang; GAO Hong-wei (浙江大学学报. 农业与生命科学版, 2002)
Planning for comprehensive land use of villages and towns constitutes the basal stratum of the overall 5-levelled planning system for land use in our country. Up to present, however, we are still lacking in a technical standard for mapping as applied to comprehensive land use planning in villages and towns. This study was dedicated to related problems with emphasis on working out a standard for base map and methodological aspects of mapping in comprehensive land use planning at village and town level. We concluded that, digitalized base map of land use created in accordance with the 1∶2000 scaled topographic map is a reasonable choice at the present stage.